IMPLEMENTATION OF ‘’PESANTREN KILAT’’ ACTIVITIES DURING RAMADAN TO DEVELOP THE PERSONALITY OF INMATES IN CLASS IIA PRISON BENGKULU - Khalifah, Bani; Yuska, Syahrial (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study examines the implementation of the Pesantren Kilat (short-term Islamic boarding school) program during Ramadan to develop the personality of prisoners at Class IIA Bengkulu Penitentiary. This research employed a qualitative method, collecting data through field observations, interviews, and literature studies. Data analysis was conducted using data reduction techniques and the NVIVO 12 software to identify themes and keyword frequencies such as "pesantren" and "penitentiary." The findings revealed that the program was well-structured, involving students, instructors, and a clear schedule, despite challenges related to limited human resources within the penitentiary. However, the involvement of external instructors ensured the smooth operation of the program. The results indicate a high level of enthusiasm among prisoners in participating in the program to deepen their understanding of Islam. The Pesantren Kilat-based coaching was effective in enhancing their religious comprehension and behavior, though challenges such as the lack of voluntary participation from some prisoners were observed. This program is expected to be an effective step in facilitating positive character development and reducing recidivism, enabling prisoners to become better individuals and contribute to society after completing their sentences. Keywords: Implementation; Coaching; Pesantren Kilat; Prisoners; Penitentiary